Spatial imbalances in the United Kingdom after the Millennium: a focus on the cities - Zsuzsanna Zsibók (DETUROPE)
During the recovery after the economic crisis, much academic and policy attention was diverted to the role of cities as growth hubs all over Europe and the world. Significant economic disparities are a longstanding problem for the United Kingdom as a whole, which have been growing for decades and are remarkably high among the most developed OECD and EU countries. To investigate recent spatial processes, the methodology of our research relies on comparative spatial data analysis and literature review. Our analyses will cover the issue of a spatially more balanced development based on the “northern powerhouse” initiative which builds upon the collective strength of the cities in the North. Addressing the ‘national’ problem of regional inequalities, spatial rebalancing is assumed to be inevitable, especially in the light of the new economic and regional challenges posed by the Brexit decision.